Subacute Cutaneous Lupus Erythematosus Coexisting in a Patient with Plaque Psoriasis. Issue 2 (March 2017) - Kim, Esther K.; Hashim, Peter W.; Khattri, Saakshi
Subacute cutaneous lupus erythematosus (SCLE) is a form of cutaneous lupus erythematosus that is characterized by nonscarring, erythematous, annular eruptions occurring mainly on sun-exposed areas. The incomplete understanding of SCLE creates challenges in diagnosis and treatment. This report describes the rare case of SCLE co-existing with plaque psoriasis.